Interaction of Shigella flexneri IpaC with Model Membranes Correlates with Effects on Cultured Cells - Tran, Ngoc (American Society for Microbiology, 2000)
Invasion of enterocytes by Shigella flexneri requires the properly timed release of IpaB and IpaC at the host-pathogen interface; however, only IpaC has been found to possess quantifiable activities in vitro. We demonstrate here that when added to cultured cells, purified IpaC elicits cytoskeletal changes similar to those that occur during Shigella invasion. This IpaC effect may correlate with its ability to interact with model membranes at physiological pH and to promote entry by an ipaC mutant of S. flexneri.